2001
DOI: 10.1093/humrep/16.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal factors of infertility in candidate couples for ICSI: an equal risk of constitutional aberrations in women and men*

Abstract: To assess the frequency of chromosomal aberrations in French candidates for intracytoplasmic sperm injection (ICSI), and to explore the existence of a female chromosomal factor in some cases of couple infertility, a collaborative retrospective clinical and cytogenetic study was performed, launched by the Association des Cytogénéticiens de Langue Franciaise (ACLF). The karyotypes of 3208 patients [2196 men (68.4%), 1012 (31.6%) women] included in ICSI programmes over a 3-year period in France were collected. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
114
4
20

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 32 publications
11
114
4
20
Order By: Relevance
“…Sex chromosome abnormalities are an important cause of male infertility [23], [24] . Intracytoplasmic sperm injection (ICSI) is an effective therapeutic method, especially in couples with male infertility and/or unsuccessful in vitro fertilization (IVF) experiences [23] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sex chromosome abnormalities are an important cause of male infertility [23], [24] . Intracytoplasmic sperm injection (ICSI) is an effective therapeutic method, especially in couples with male infertility and/or unsuccessful in vitro fertilization (IVF) experiences [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic evaluation of couples prior to ICSI shows thatboth genders are equally at risk for sex chromosome abnormalities. An increased incidence of the 47, XYY karyotype in infertile males has been reported [24] , although the majority of individuals with this karyotype are fertile and show normal spermatogenesis [24], [25] . In those males who have spermatogenetic failure, abnormalities of azoospermia factor genes in the euchromatic region on the long arm of the Y chromosome (Yq) have been reported [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infertility is an important health problem that affects about 10-15% of all couples attempting pregnancy [1,2]. Sex chromosome abnormalities are an important cause of male infertility [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Structural defects include balanced and unbalanced translocations as well as inversions and deletions. Using karyotype analysis, Gekkas et al 5 reported that 6.1% of unselected men (134 of 2,190) who needed ICSI had a somatic chromosomal rearrangement. The frequency of somatic (blood) chromosome abnormalities was higher in men with azoospermia (18.71%) than in men with severe (14.55%) or moderate (2.37%) oligozoospermia.…”
mentioning
confidence: 99%